2015
DOI: 10.3109/15368378.2015.1043557
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative mechanisms of biological activity of low-intensity radiofrequency radiation

Abstract: This review aims to cover experimental data on oxidative effects of low-intensity radiofrequency radiation (RFR) in living cells. Analysis of the currently available peer-reviewed scientific literature reveals molecular effects induced by low-intensity RFR in living cells; this includes significant activation of key pathways generating reactive oxygen species (ROS), activation of peroxidation, oxidative damage of DNA and changes in the activity of antioxidant enzymes. It indicates that among 100 currently avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
0
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(141 citation statements)
references
References 168 publications
5
119
0
17
Order By: Relevance
“…These free radicals or ROS are an intrinsic part of the cellular signaling cascades (Forman et al, 2014). Therefore, low-intensity RF-EMR is an agent of ROS production, which may induce harmful effects in living cells (Yakymenko, et al, 2015). Additionally, microwaveinduced oxidative stress may produce ROS that are reported to be the main cause of cellular damage or tissue injury (Dasdag et al, 2008;Behari, 2009, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…These free radicals or ROS are an intrinsic part of the cellular signaling cascades (Forman et al, 2014). Therefore, low-intensity RF-EMR is an agent of ROS production, which may induce harmful effects in living cells (Yakymenko, et al, 2015). Additionally, microwaveinduced oxidative stress may produce ROS that are reported to be the main cause of cellular damage or tissue injury (Dasdag et al, 2008;Behari, 2009, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Increasing evidence has demonstrated that exposure to RF-EMFs radiation may induce oxidative stress [25], followed by cellular oxidative damage, i.e., oxidative DNA damage [26,27]. Oxidative stress is a condition induced by oxygen and oxygen-derived free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…• Salivary gland tumors [7,8] • Dizziness and migraines [9] • Less sleep and poor sleep quality [10] • Increases and decreases in production of specific proteins in human cells [11] • Decreased sperm count and quality [12][13][14] • Skin irritation, especially on the face (this is a condition known as electrohypersensitivity) [15,16] • Behavioral problems and increased chance of cancer tumor development in children.…”
Section: Increases Risk Of Eye Vision Problemsmentioning
confidence: 99%